Probing electric and magnetic fields with a Moiré deflectometer - Lansonneur, Pierre; Bräunig, Philippe; Demetrio, Andrea; Müller, Simon R.; Oberthaler, Markus K. (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2017)
A new contact-free approach for measuring simultaneously electric and magnetic field is reported, which considers the use of a low energy ion source, a set of three transmission gratings and a position sensitive detector. Recently tested with antiprotons (Aghion et al., 2014) [1] at the CERN Antiproton Decelerator facility, this paper extends the proof of principle of a moiré deflectometer (Oberthaler et al., 1996) [2] for distinguishing electric from magnetic fields and opens the route to precision measurements when one is not limited by the ion source intensity. The apparatus presented, whose resolution is mainly limited by the shot noise is able to measure fields as low as 9mVm−1Hz−1/2 for electric component and 100μGHz−1/2 for the magnetic component. Scaled to 100nm pitch for the gratings, accessible with current state-of-the-art technology [3], the moiré fieldmeter would be able to measure fields as low as 22μVm−1Hz−1/2 and 0.2μGHz−1/2.
Gesehen am 28.03.2018